Regulation of epithelial chloride transport by phospho-tyrosine-initiated protein networks - Loureiro, C.A. (2019)
Ion transport is crucial for cell volume regulation by compensating variations in extracellular tonicity, playing an important role in maintaining the structural integrity and intracellular milieu in cells. These functions require a dynamic, spatio-temporally coordinated regulation of ion transport, which occurs in cells by two mechanisms: first, the amount of channel or cotransporter inserted into the plasma membrane (PM) from a pool of endosomal storage vesicles, and second, the ion transport activity regulated by post-translational modifications such as phosphorylation of channel or transporter proteins. Previous results from the host laboratory showed that phosphorylation by spleen tyrosine kinase (SYK) of Tyr512 in the NBD1 domain regulates PM abundance of CFTR, the chloride channel involved in cystic fibrosis. The main objective of this PhD project was to identify phospho-tyrosine-binding proteins involved in the regulation of chloride transport proteins and the underlying molecular mechanism. First, it was found that besides CFTR two further renal ion cotransporters, NKCC2 and KCC3, are phosphorylated by SYK in vitro on an N-terminal tyrosine residue and that experimental manipulation of either SYK expression levels or its catalytic activity affect the cell surface abundance of these cotransporters. Interestingly, the very same phosphorylation pathway leads to a decrease in NKCC2 but to an increase in KCC3 PM levels. Second, the underlying biochemical mechanism was identified using peptide pulldown assays followed by mass spectrometry and revealed that the adaptor protein SHC1 binds to phospho-tyrosine in NKCC2, KCC3 and CFTR through its PTB domain. Upon depletion of endogenous SHC1 expression, KCC3 decreased at the PM, whereas NKCC2 and CFTR levels increased. In the case of phosphorylated NKCC2, SNX27 and NCK1 were identified as additional binding partners. Lastly, SHC1 was shown to form a complex with CFTR following activation of protein kinase SYK, but does not affect the PM level of the most frequent mutant F508del-CFTR. The results described in this work identified a novel SYK/SHC1 pathway that regulates the cotransporters NKCC2 and KCC3 and the chloride channel CFTR and have potential biomedical implications for the identification of new therapeutic targets in diseases like hypertension or cystic fibrosis, or those involving regulation of cell volume.